Leptin and soluble leptin receptor in association with gestational diabetes: a prospective case–control study - Mosavat, Maryam; Omar, Siti Zawiah; Tan, Peng Chiong; Razif, Muhammad Fazril Mohamad; Sthaneshwar, Pavai (Springer Verlag (Germany), 2018)
Purpose: To assess the association of serum leptin and its receptor (SLeptinR) with the risk of gestational diabetes mellitus (GDM) and to evaluate the longitudinal circulation of these peptides in pregnancy. Methods: This study consisted of 53 subjects diagnosed with GDM and 43 normal glucose tolerance (NGT) pregnant women. Serum leptin and SLeptinR were measured at 24–28 weeks, prior and after delivery, and post-puerperium. Results: Lower levels of leptin and SLeptinR were observed in GDM compared to NGT. Leptin [OR 0.97 (95% CI 0.94–1.0)] and SLeptinR [OR 0.86 (95% CI 0.79–0.93]) were inversely associated with GDM. Participants in the lowest tertile for leptin and SLeptinR had a 2.8-fold (95% CI 1.0–7.6) and a 5.7-fold (95% CI 1.9–17.3) higher risk of developing GDM compared with the highest tertile, respectively. These relationships were attenuated after adjustment for covariates. In both the groups, peak leptin was observed at 24–28 weeks, decreasing continuously during pregnancy (p > 0.05) and after delivery (p < 0.017). SLeptinR level increased (p < 0.001) during pregnancy and decreased (p < 0.005) after delivery in GDM, however, levels remained the same in NGT. In GDM, leptin and SLeptinR was positively and inversely correlated with BMI and HOMA-IR at 24–28 weeks and post-puerperium, respectively. The cord levels of both leptin and SLeptinR were lower than maternal levels. There were no significant differences in serum cord leptin and SLeptinR levels between the groups. Conclusion: Leptin and SLeptinR are independently and inversely associated with GDM. Lower levels of these peptides may play an important role in the pathophysiology of GDM and pre-diabetic state in post-puerperium.